2005
DOI: 10.1113/jphysiol.2004.082180
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of excitation–contraction coupling and titin by endogenous Ca2+‐activated proteases in toad muscle fibres

Abstract: ] to 10 nM, and was almost completely inhibited by 1 mM leupeptin but not by 10 µM calpastatin. Muscle homogenates preactivated by Ca 2+ exposure also evidently contained a diffusible factor that caused damage to passive force production in a Ca 2+ -dependent manner. Western blotting showed that: (a) calpain-3 was present in the skinned fibres and was activated by the Ca 2+ exposure, and (b) the Ca 2+ exposure in stretched skinned fibres resulted in proteolysis of titin. We conclude that the disruption of EC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 50 publications
3
61
2
Order By: Relevance
“…In their review, Allen and Westerblad (3) propose elevated inorganic phosphate to be the key factor by leading to the precipitation of calcium phosphate. Alternatively excitation coupling may be disrupted by calciumactivated proteases (40). Our experimental findings provide some evidence for supporting the former because both the concentric and eccentric exercises can be expected to result in roughly similar profiles of activation (24) and calcium release (there is a moderate decrease of EMG activity in eccentric contractions) (21) but with very different use of metabolic energy.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In their review, Allen and Westerblad (3) propose elevated inorganic phosphate to be the key factor by leading to the precipitation of calcium phosphate. Alternatively excitation coupling may be disrupted by calciumactivated proteases (40). Our experimental findings provide some evidence for supporting the former because both the concentric and eccentric exercises can be expected to result in roughly similar profiles of activation (24) and calcium release (there is a moderate decrease of EMG activity in eccentric contractions) (21) but with very different use of metabolic energy.…”
Section: Discussionsupporting
confidence: 50%
“…The twitch response at 20 min after 20 contractions was 72 Ϯ 2.2%, and after 80 contractions it was 50 Ϯ 6.0% control (n ϭ 5). There was no significant difference between 40 A reduction in electrically induced EMG (M wave) following fatiguing electrical stimulation has been reported in both rats (23) and humans (25) with a maximum depression of ϳ50% after 60 min. Figure 3A shows that in the present experiments, there was also a decline in the M wave but that this was Ͻ20% for both concentric and eccentric contractions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Much of the ubiquitous calpain is freely diffusible, but some is normally bound at triad junction (182), and raising [Ca 2ϩ ] within the physiological range increases calpain binding there (322,367). Ca 2ϩ -dependent uncoupling is prevented in toad skinned fiber by leupeptin, a calpain inhibitor, but only at low [Ca 2ϩ ] when the uncoupling proceeds slowly (254,451). Calpain inhibitors, however, were not found to prevent either long-duration fatigue in mouse fibers (89) or hypotonic-induced PCD in frog fibers (69).…”
Section: Prolonged Reduction In Ca 2؉ Releasementioning
confidence: 98%
“…Calpain inhibitors, however, were not found to prevent either long-duration fatigue in mouse fibers (89) or hypotonic-induced PCD in frog fibers (69). Calpain inhibitors such as leupeptin are quite poor at inhibiting in situ calpain-dependent proteolysis of structural proteins (141), unless used at very high concentration (241,322,451), so it still seems possible that they might play a role in the Ca 2ϩ -dependent uncoupling. It is known, however, that Ca 2ϩ -dependent uncoupling does not involve proteolysis of the DHPRs, RyRs, or another junctional protein, triadin (254).…”
Section: Prolonged Reduction In Ca 2؉ Releasementioning
confidence: 99%
“…Previous studies demonstrated that ischemiainduced stress increased [Ca 2ϩ ] i in skeletal muscle (32). The importance of prolonged elevation of resting [Ca 2ϩ ] i after contractions likely relates to the muscle weakness and/or activation of proteolytic pathways (12,55,56 homeostasis may be associated with the compromised SR function. In previous studies using cardiac muscle, decreased SR Ca 2ϩ transport and SR Ca 2ϩ content have been detected in animal diabetic models (13,19).…”
Section: Effects Of Muscle Contractions On [Ca 2ϩ ] I Accumulationmentioning
confidence: 99%